Early Hypertension and Diabetes after Living Kidney Donation: A National Cohort Study - Holscher, Courtenay M. (Transplantation, 2019)
BACKGROUND: Living kidney donors have an increased risk of end-stage renal disease, with hypertension and diabetes as the predominant causes. In this study, we sought to better understand the timeline when these diseases occur, focusing on the early postdonation period. METHODS: We studied 41 260 living kidney donors in the US between 2008–2014 from the SRTR and modeled incidence rates and risk factors for hypertension and diabetes. RESULTS: At 6-months, 1-year, and 2-years postdonation, there were 74, 162, and 310 cases of hypertension per 10 000 donors. Donors who were older (per 10 years, aIRR 1.40, 95% CI 1.29–1.51), male (aIRR 1.31, 95% CI 1.14–1.50), had higher BMI (per 5 units, aIRR 1.29, 95% CI 1.17–1.43), and were related to their recipient (first degree relative, aIRR 1.28, 95% CI 1.08–1.52; spouse, aIRR 1.34, 95% CI 1.08–1.66) were more likely to develop hypertension, while donors who were Hispanic/Latino were less likely (aIRR 0.71, 95% CI 0.55–0.93). At 6-months, 1-year, and 2-years, there were 2, 6, and 15 cases of diabetes per 10 000 donors. Donors who were older (per 10 years, aIRR 1.42, 95% CI 1.11–1.82), had higher BMI (per 5 units, aIRR 1.52, 95% CI 1.04–2.21), and were Hispanic/Latino (aIRR 2.45, 95% CI 1.14–5.26) were more likely to develop diabetes. CONCLUSIONS: In this national study, new-onset diabetes was rare, but 3% of donors developed hypertension within 2 years of nephrectomy. These findings reaffirm that disease pathways for kidney failure differ by donor phenotype and estimate the population most at-risk for later kidney failure.